Physical and Psychological Health Following Military Sexual Assault Recommendations for Care, Research, and Policy - Farris, Coreen (RAND Corporation, 2013)
This paper reviews data on the prevalence of sexual assault among servicemembers, predictors of disclosure, efforts to improve disclosure, victim needs, and DoD efforts to provide necessary resources in the immediate aftermath of a sexual assault.